Poverty and Democratic Consolidation in Nigeria: Issues, Challenges and the Way Forward - Adamu, Abdulrahman (University of Nigeria Journal of Political Economy, 2022)
It is fundamental to note that high level of poverty in any democratic society affects the consolidation of the system. This is because democracy cannot be sustained or consolidated in a society where there is extreme poverty, hunger and starvation. This study is an examination of the potential challenges of poverty to the consolidation of Democracy in Nigeria. The paper adopts a historical/descriptive method of enquiry and generates data largely from books, journal articles, magazines/newspapers and the Internet. It argues that in Nigeria, the inability of successive governments to make frantic efforts towards harnessing the enormous human and material potentials of the country to improve the standard of living of the citizens is the actual cause of poverty. The paper concludes that the phenomenon of poverty in Nigeria is not new and its history is as old as the history of the people believing that its modern manifestations are linked directly to the history of western imperialism. It concludes further that democracy cannot be consolidated in an impoverished society where people live below the poverty line and where diseases and famine are prominent. The study suggests the way forward to include among others that for Nigerian democracy to be consolidated, the political elite must ensure good governance via judicious use of available resources, provision of social amenities and critical infrastructures, ensure periodic free, fair and credible elections, promote transparency and accountability so as to reduce poverty.